DETERMINAN KINERJA AKADEMIK PENYELENGGARAAN PENDIDIKAN PROGRAM PASCASARJANA UNNES - Widodo, Joko (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
The academic performance of an institution empirically is determined by six performance indicators, namely: infrastructure-educational facilities (tangibles); reliability faculty and staff (reliability), responsiveness of faculty and academic staff (responsibility); treatment of faculty and staff to students (assurance); understanding the students’ interests (empathy), and student satisfaction (satisfaction). The problems of this study are; (1) how is the students’ satisfaction toward academic service? (2) How is the performance of academic program? How high is academic performance? What factors affect the performance? The objectives of this research are (1) to describe students’ satisfaction toward academic service, (2) to describe the performance of academic program, to describe academic performance, and to describe the factors which affect academic performance at Post Graduate Programs in Semarang State University. The method of this research was description. The results of the study were; the six academic performance indicators are in good category, students’ satisfaction toward academic service both in the scope of study program and Post Graduate Programs are classified in good category, and the description of study programs’ academic performance result generally was in good category.